2022
DOI: 10.1021/acs.estlett.2c00599
|View full text |Cite
|
Sign up to set email alerts
|

Model Evaluation of Secondary Chemistry due to Disinfection of Indoor Air with Germicidal Ultraviolet Lamps

Abstract: Air disinfection using germicidal ultraviolet light (GUV) has received increasing attention during the COVID-19 pandemic. GUV uses UVC lamps to inactivate microorganisms, but it also initiates photochemistry in air. However, GUV's indoorair-quality impact has not been investigated in detail. Here, we model the chemistry initiated by GUV at 254 ("GUV254") or 222 nm ("GUV222") in a typical indoor setting for different ventilation levels. Our analysis shows that GUV254, usually installed in the upper room, can si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 50 publications
(86 reference statements)
4
27
0
Order By: Relevance
“…O 3 itself is a major air pollutant causing excess deaths at levels below those in occupational guidelines of 50–100 ppb. , More importantly, it can also lead to formation of other pollutants including particulate matter, whose excess death impacts can be many times higher than those of O 3 itself (section S6). , O 3 production by GUV222 lamps thus can be a major concern, at least under low-ventilation conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O 3 itself is a major air pollutant causing excess deaths at levels below those in occupational guidelines of 50–100 ppb. , More importantly, it can also lead to formation of other pollutants including particulate matter, whose excess death impacts can be many times higher than those of O 3 itself (section S6). , O 3 production by GUV222 lamps thus can be a major concern, at least under low-ventilation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review concluded that O 3 generation by KrCl excimer lamps was minimal: for example, a 12 W lamp was estimated to take 267 h to produce 4.5 ppb O 3 in a 30 m 3 room in the absence of losses . A recent modeling paper estimated O 3 generation to be nearly two orders of magnitude faster, but those findings have not been confirmed experimentally. There is also discussion in the literature whether O 3 is mainly formed by the UVC radiation or by discharges in electrical connections …”
Section: Introductionmentioning
confidence: 99%
“…As discussed previously, UVC has been used as a sterilization method in hospitals due to its germicidal effects and ability to deactivate some viruses. Moreover, with the recent Coronavirus Disease 2019 (COVID-19) pandemic, UVC disinfection systems have seen a spike in sales, necessitating further studies for the safe usage of UVC radiation. Many of the safety studies performed to date have focused on the impact of direct radiation on DNA. ,, However, recent studies and the work presented here shows that safety studies should also consider secondary reactions caused by UVC irradiation of organic molecules, including those resulting from human emissions in indoor environments.…”
Section: Resultsmentioning
confidence: 96%
“…). ,, As mentioned previously, lactic acid is prevalent in indoor environments due to human emissions, where it will likely be found on surfaces or in aerosols due to its low vapor pressure. , We therefore suggest that lactic acid photolysis may be occurring in such indoor environments and could produce harmful byproducts during these UVC sterilization procedures. However, most photochemical studies address photochemistry in the modern Earth’s outdoor environment where UVC is not available, and thus, few studies have addressed photochemistry using radiation with energies equal to UVC sterilization procedures. Previous work by Deal et al and others ,, suggests that lactic acid may be photoactive under these conditions and, if so, will produce harmful byproducts (e.g., CO and formic acid) that may remain even after the UVC sterilization is complete, thereby posing an indirect risk to human health. It is therefore important to understand the products and mechanisms of lactic acid photolysis in environments which more accurately model indoor environments (i.e., in the presence of oxygen).…”
Section: Introductionmentioning
confidence: 99%
“…GUV has been in use in many applications across DoD [73], in hospitals for infection control and to some extent for short-term or temporary exposure in public spaces. At this time a debate remains unresolved about long-term safety and appropriateness for extended, daily use of GUV [58] especially in regards to excessive generation of volatile organic compounds (VOC) and formation of secondary aerosols [59] [60] which may be carcinogenic [61]. 4 is used to estimate the combination effect on reduction of infectious particle concentration (P2P contagion) using both 24x7x365 detection with 12 ACH air filtration in the room (Figure 8).…”
Section: Portable Air Filtrationmentioning
confidence: 99%